2022
DOI: 10.1111/lam.13595
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antibiofilm and anti-quorum sensing activities of Muntingia calabura L. leaf extract against Pseudomonas aeruginosa

Abstract: The aim of this study was to evaluate the phytochemicals, antioxidant, antibacterial and anti‐quorum sensing (QS) properties of methanol extract of Muntingia calabura L. leaves against biofilm‐forming strain Pseudomonas aeruginosa. The antioxidant potential of M. calabura methanol leaf extract was evaluated using a radical scavenging assay. Since the findings were so promising, the study aims to screen the phytochemical profiles using qualitative and quantitative approaches and to expand the investigation to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The lowest anti-biofilm activity was obtained against B. cereus ATCC 1178 (65.220.24%) in 95% ethanolic and 75% acetonic extracts and S. typhimurium ATCC 13311 (68.960.28%) in aqueous extract. The study of MosaChristas et al (2022) showed that M. calabura methanol leaves extracts were most potent anti-biofilm formation of P. aeruginosa 34 . Enterococcus faecalis is a common biofilm former usually implicated in urinary tract infections, wound infections, and dental infections 35 .…”
Section: Anti-biofilm Activitymentioning
confidence: 99%
“…The lowest anti-biofilm activity was obtained against B. cereus ATCC 1178 (65.220.24%) in 95% ethanolic and 75% acetonic extracts and S. typhimurium ATCC 13311 (68.960.28%) in aqueous extract. The study of MosaChristas et al (2022) showed that M. calabura methanol leaves extracts were most potent anti-biofilm formation of P. aeruginosa 34 . Enterococcus faecalis is a common biofilm former usually implicated in urinary tract infections, wound infections, and dental infections 35 .…”
Section: Anti-biofilm Activitymentioning
confidence: 99%
“…Ferula oil and Dorema oil, belonging to the Apiaceae family, and grapefruit ( Citrus paradisi ) essential oils can produce flavonoids, which were found to reduce virulence factor production and interfere with the communication between bacteria [ 157 , 158 ]. Extracts from other natural sources such as the methanol extract of T. bellerica and extracts of Oscillatoria subuliformis , Moringa oleifera , Cuphea carthagenensis , Coccinia indica , and Muntingia calabura L. leaves, have been reported to interfere with the biofilm development and QS of P. aeruginosa [ 159 , 160 , 161 , 162 , 163 , 164 ]. The extracted metabolites of the endolichenic fungi (ELF) Aspergillus quandricinctus of Usnea longissima affect the activities of elastase and protease and prevent the biofilm formation of P. aeruginosa [ 165 ].…”
Section: Inhibition Mechanism Undeterminedmentioning
confidence: 99%